Carbon‐Enriched Amorphous Hydrogenated Boron Carbide Films for Very‐Low‐k Interlayer Dielectrics. (21st September 2017) - Nordell, Bradley J.; Nguyen, Thuong D.; Caruso, Anthony N.; Purohit, Sudhaunshu S.; Oyler, Nathan A.; Lanford, William A.; Gidley, David W.; Gaskins, John T.; Hopkins, Patrick E.; Henry, Patrick; King, Sean W.; Paquette, Michelle M.
Abstract: A longstanding challenge in ultralarge‐scale integration has been the continued improvement in low‐dielectric‐constant (low‐ k ) interlayer dielectric materials and other specialized layers in back‐end‐of‐the‐line interconnect fabrication. Modeled after the success of carbon‐containing organosilicate materials, carbon‐enriched amorphous hydrogenated boron carbide (a‐B x C:H y ) films are grown by plasma‐enhanced chemical vapor deposition from ortho ‐carborane and methane. These films contain more extraicosahedral sp 3 hydrocarbon groups than nonenriched a‐B x C:H y films, as revealed by FTIR and NMR spectroscopy, and also exhibit lower dielectric constants than their nonenriched counterparts, notably due to low densities combined with a low distortion and orientation contribution to the total polarizability. Films with dielectric constant as low as 2.5 are reported with excellent electrical stability (leakage current of 10 −9 A cm −2 at 2 MV cm −1 and breakdown voltage of >6 MV cm −1 ), good thermal conductivity of 0.31 ± 0.03 W m −1 K −1, and high projected Young's modulus of 12 ± 3 GPa. These properties rival those of leading SiOC:H materials, and position a‐B x C:H y as an important complement to traditional Si‐based materials to meet the complex needs of next‐generation interconnect fabrication. Abstract : Carbon‐enriched amorphous hydrogenated boron carbide films are demonstrated with dielectric constant ( k ) as low as 2.5—attributed to low densities combined with network‐rigidifying CH2 bridging groups—as well as excellent electrical, thermal, and mechanical properties, rivaling those of state‐of‐the‐art silicon‐based low‐ k dielectric materials.